Performance of local aggregate in high friction surface treatment - Zahir, Humaira (Kansas State University, 2016)
Road surfaces may prematurely lose pavement friction due to polished aggregates on sharp horizontal curves, steep grades, or near intersections resulting in vehicle skidding. The problem gets exacerbated during wet weather. The Federal Highway Administration (FHWA) estimates that about 70% of wet pavement crashes can be prevented or minimized by improving pavement friction. High Friction Surface Treatment (HFST), a specially-designed thin surface application of hard aggregates and thermosetting resins like epoxy, has been proven to be an effective method to increase road surface friction. Calcined bauxite has been predominantly used in the United States as the hard aggregate in combination with an epoxy binder for HFST. However, this treatment is expensive since the calcined bauxite is imported. The objective of this study is to evaluate the performance of a local aggregate in HFST. Slab specimens of hot-mix asphalt (HMA) were compacted in the laboratory and treated with HFST systems incorporating both calcined bauxite and a local, hard aggregate, Picher Oklahoma flint aggregate. The treated HMA specimens were then tested with a Dynamic Friction Tester (DFT) and a Circular Track Meter (CTM) to determine the frictional coefficient and texture depth, respectively. Also, Hamburg Wheel Tracking Device Testing were conducted on these HFST systems to evaluate wearing resistance under repetitive wheel load. Field measurements of texture depths on HFST were also done. Statistical analysis was performed to compare the performance of high friction surfaces prepared with different aggregate epoxy combinations. The results show that flint aggregate can be a suitable substitute for the calcined bauxite in HFST. Field measurements also showed marked improvements in texture depth with HFST.
Keywords: Friction; Skid resistance; High friction surface treatment; Local aggregate